MODEL AKTIVITAS BELAJAR GERAK BERBASIS PERMAINAN SEBAGAI MATERI AJAR PENDIDIKAN JASMANI - Rif'iy Qomarrullah (Universitas Negeri Semarang, 2015)
This study aims to describe and develop models of innovative teaching physical education. Research development produced outcomes and learning processes student in the form of products obtained by: 1) Summary of the percentage of the validation results of the expert evaluation questionnaires obtained an average score of 47, with a percentage of 79% which is quite valid category, therefore the model of motion based game learning activities can be used as the physical education teaching materials in class I elementary school. 2) The data value of the students' learning ability, that the model is tested on a small scale trial gained mastery of student learning outcomes at 68.97%, which means good and on a wider scale trials mastery learning students gained an average of 76%, which means good, so it can be understood if the model developed is able to contribute significantly positive in the ability of student learning outcomes. Based on data from the pre-test showed the level of mastery learning students only reached 36.36 % , and thereafter the application of product models , at the stage of post-test showed the level of mastery learning students amounted to 86.37 % . That difference is the effect of the application development model, where the effect of the model developed a positive impact on the level of mastery learning students